Unit profit margins along post-Keynesian lines: from Sraffa, Kalecki, Robinson to Eichner, Wood, Harcourt and Kenyon. Issue 1 (2nd January 2023) - Melmiès, Jordan
Abstract: This article offers a retrospective reading of the evolution of post-Keynesian authors on the determination of corporate unit profit margins. It shows that this theory was essentially structured into three stages. The first stage is based on the so called imperfect competition theory and/or the degree of monopoly in the 1920s and 1930s, which was based in turn on an indirect approach and profit maximisation. This was followed by a second period of distancing from and questioning of this work, before a third period of structuring and convergence towards a more direct and inclusive approach focussing on growth and self-financing of investment in the 1970s. This evolution raises issues in terms of analysis and economic policy.